Resisting social pressure in the household using mobile money: experimental evidence on microenterprise investment in Uganda - Riley, E (University of Oxford, 2022)
Intra-household sharing pressure has been shown to be a key constraint on female enterprise growth in developing countries. However, the growth of digital financial services offers a new way to reduce this sharing pressure. In this paper, I examine whether changing the form that a microfinance loan is disbursed in, from cash to directly onto a digital account, enables female microfinance borrowers to grow their businesses. Using a field experiment of 3,000 female borrowers in Uganda, I compare the disbursement of a loan as cash to the disbursement of a loan onto a mobile money account. After 8 months, women who received their microfinance loan on the mobile money account had 11% higher levels of business capital and 15% higher business profits compared to a control group who received their loan as cash. Total household income and consumption were also higher. Impacts were greatest for women who experienced pressure to share money with others in the household at baseline, suggesting that providing the loan in a digital account reduces sharing of the loan with others, to the benefit of both the woman's business and household. This indicates that widespread mobile money services can be utilised to counteract the negative impact of sharing pressure on the performance of female-owned enterprises.